Personal Branding pada Konten Feeds Fashion Blogger @tamaradai dan @elikaboen di Instagram - Winata, Cecilia Liusca; Wibowo, S. Kunto Adi; Fuady, Ikhsan (Universitas Prof. Dr. Moestopo (Beragama), 2024)
Thanks to the emergence of Instagram as a social media platform, the popularity of fashion bloggers has been increasing, and they have utilized the power of Instagram to build their personal branding based on their expertise in specific fields. By effectively building and promoting their personal branding, fashion bloggers can enhance their visibility, attract new followers, and generate higher income and engagement rates. This research aims to analyze the content of two prominent fashion bloggers, @tamaradai and @elikaboen, on Instagram. The study examined 128 photo posts obtained through sample size calculation. Hypothesis testing was conducted using quantitative descriptive statistical analysis and Pearson Chi-Square test with IBM SPSS software version 26. Data collection involved observing image-based fashion blogger content and manually coding the data using a coding book. The findings indicate that the fashion theme is the most dominant in the content feeds of both fashion bloggers, and the majority of posts do not contain hashtags or mentions of brands or other entities. The statistical analysis results demonstrate a significant relationship between certain image content categories and the external relationship category, particularly in terms of tag usage and mentions with '@'.